Genome-wide identification and functional characterization of CDPK gene family reveal their involvement in response to drought stress in Gossypium barbadense - Shi,Guangzhen; Zhu,Xinxia (PeerJ, 2022)
Background Calcium dependent protein kinases (CDPKs) are a class of important calcium signal sensing response proteins, which play an important regulatory role in response to abiotic stress. However, researchers have not been excavated CDPKs’ role in drought in sea-island cotton(Gossypium barbadense L. ‘H7124’). Results Eighty-four CDPK genes have been identified in G. barbadense. These GbCDPK genes are unevenly distributed on 26 chromosomes, and segmental duplication is the significant way for the extension of CDPK family. Also, members within the same subfamily share a similar gene structure and motif composition. There are a large number of cis-elements involved in plant growth and response to stresses in the promoter regions of GbCDPKs. Additionally, these GbCDPKs show differential expression patterns in cotton tissues. The transcription levels of most genes were markedly altered in cotton under heat, cold, salt and PEG treatments, while the expressions of some GbCDPKs were induced in cotton under drought stress. Among these drought-induced genes, we selected GbCDPK32, GbCDPK68, GbCDPK74, GbCDPK80 and GbCDPK83 for further functional characterization by virus-induced gene silencing (VIGS) method. Conclusions In conclusion, the principal findings of this prospective study are that CDPKs were associated with drought. These findings provide a solid foundation for the development of future molecular mechanism in sea-island cotton.
Keywords: Identification; CDPKs; Drought; Stress; Gossypium barbadense